Buyer-supplier relationships and the adoption of electronic marketplaces - Wang, Shan; Archer, Norman P.; McMaster University, Michael G. DeGroote School of Business (My University, 2003)
Despite the high expectation that researchers and practitioners put on business-to-business electronic marketplaces (EMs), they have not prospered as expected. Relatively high setup and maintenance costs, the need for organizational changes, uncertainty of investment, and transaction risk are among the reasons mentioned most often that deter the adoption ofEMs.
This paper argues that buyer-supplier relationships play a significant role in the adoption decision. Although EMs, by acting more than as a market, make both long- and short-term relationships efficient, this efficiency gain does not necessarily lead firms to favor an EM strategy. Certain aspects of incentives also complicate the decision. A framework is provided to identify the elements (industry type, inter-organizational relationship type, and transaction and product attributes) that affect relationships and thus influence the adoption decision. A case study, which compares EM adoption decisions in fragmented and concentrated industries, is presented as a preliminary verification of the framework.
42 p. : ; Includes bibliographic references (p. 35-37). ; "January, 2003."
Keywords: Adoption; Buyer-supplier relationships; Electronic marketplaces; Business; Business; Electronic commerce Internet marketing Relationship marketing